EVALUASI KEBERHASILAN PELAKSANAAN PROGRAM BEDAH DESA AAN DI KABUPATEN KLUNGKUNG-BALI. - I Komang Yogi Indra Prama Mertha; I Komang Gede Santhyasa; Komang Wirawan (UNHI PRESS, 2022)
Klungkung Regency is the first region to implement the Village Surgery program in Bali. Recorded since January 15, 2016 until now the Village Surgery program in Klungkung Regency has touched 38 villages from 58 villages and 6 villages, one of which is Aan Village. The Village Surgery program covers 4 aspects, namely Education, Health, Social Affairs and Infrastructure.Therefore, it is very important to conduct research evaluation of the success of village surgery program implementation. By conducting an evaluation can know whether the implementation of a program is in accordance with the main objectives, which further evaluation activities can be a benchmark whether a policy or activity can be said to be worth continuing, needs to be improved or stopped activities. This research was conducted in Aan Village, Banjarangkan District, Klungkung Regency, Bali Province. Research data is obtained through observations, interviews and agency surveys. Data analysis using scoring analysis techniques.Based on the results of the research showed that the evaluation of the successful implementation of the Aan Village Surgery program in Klungkung-Bali Regency was on a score of 4 which was included in the category